Sustainable materials for electrochemical capacitors - Inamuddin, 1980-; Altalhi, Tariq; Adnan, Sayed Mohammed (John Wiley & Sons, Inc. ; Scrivener Publishing, 2023)
Sustainable Materials for Electrochemical Capacitors The book highlights the properties of sustainable materials for the production of commercial electrochemical capacitors. Sustainable Materials for Electrochemical Capacitors details the progress in the usage of ubiquitous environmentally sustainable materials. Due to their cost effectiveness, flexible forms, frequent accessibility, and environmentally friendly nature, electrochemical capacitors with significant surface areas of their carbon components are quite common. Many novel ways for using bio-derived components in highly efficient electrochemical capacitors are being established as a consequence of current research, and this book provides details of all these developments. The book provides: A broad overview of properties explored for the development of electrochemical capacitors; Introduces potential applications of electrochemical capacitors; Highlights sustainable materials exploited for the production of electrochemical capacitors; Presents commercial potential of electrochemical capacitors. Audience This is a useful guide for engineers, materials scientists, physicists, and innovators, who are linked to the development and applications of electrochemical capacitors.